Evaluasi Masalah Drainase Jalan Jendral Sudirman Kota Duri Kecamatan Mandau Kabupaten Bengkalis - Rellyadi Saputra Laset; Manyuk Fauzi; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Environmental problems are often encountered in our country at the moment is flooding during the rainy season. At the time of rain with high intensity and for a long time causing flooding in several areas in Duri City, one of which is Jalan Sudirman. Jalan Sudirman is one of the centers of economic activity in Duri City. The purpose of this study was to evaluate the drainage system, calculate the discharge and channel capacity is needed, as well as identifying problems puddle / flood at Jalan Sudirman in Duri City. Rainfall data used in the form of daily rainfall data for 11 years at the station to determine rainfall Kandis plan to use when the 10 year anniversary and plans rainfall obtained at 129.071 mm. Of the map area rainfall runoff and discharge plans in the region count to get the dimensions of the channel plan. The results of the study showed that at some point the catchment area of the existing channel has dimensions smaller than the dimensions of the channel plan. Existing channel capacity can be maximized by means of normalization, namely repair of damaged canal walls, dredging and increased sedimentation of channel dimensions. Keywords: floods, rainfall, drainage systems, channel dimensions